A comparative study of LPWAN technologies for large-scale IoT deployment - Mekki, Kais; Bajic, Eddy; Chaxel, Frederic; Meyer, Fernand (ICT express, 2019)
By 2020, more than 50 billion devices would be connected through radio communications. In accordance with the rapid growth of the Internet of Things (IoT) market, Low Power Wide Area Networks (LPWAN) have become popular as low-rate long-range radio communication technologies. Sigfox, LoRa, and NB-IoT are actually three leading LPWAN technologies that compete for large-scale IoT deployment. This paper provides a comprehensive and comparative study on these technologies as efficient solutions to connect smart, autonomous and heterogeneous devices. We show that Sigfox and LoRa have advantages in terms of battery lifetime, capacity, and cost. Meanwhile, NB-IoT offers benefits in terms of latency and quality of service. In addition, we analyze IoT success factors of these major LPWAN technologies, and we consider application scenarios and explain which technology fits best.